2023
DOI: 10.1155/2023/1375867
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Three Specific Collaborative Merging Strategies on Traffic Flow

Abstract: On-ramps are considered to be one of the common traffic bottlenecks. In order to improve the operation efficiency of on-ramps, scholars worldwide have proposed various vehicle merging strategies. In this study, we designed different rules to express three collaborative strategies and studied their impact on on-ramp systems. Cellular automata models were used to simulate the systems under different situations, and the average speed and traffic flow rate of both the main roads and ramps were analyzed. The result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…In papers [40,41], comparable studies are carried out reproducing a decrease in throughput at exits from highways and entrances to highways. The authors identified one of the main weaknesses of microscopic modeling of traffic at the exit and entrance to the highway-this is a decrease in throughput.…”
Section: Microscopic Models Of the Traffic Flowsmentioning
confidence: 99%
“…In papers [40,41], comparable studies are carried out reproducing a decrease in throughput at exits from highways and entrances to highways. The authors identified one of the main weaknesses of microscopic modeling of traffic at the exit and entrance to the highway-this is a decrease in throughput.…”
Section: Microscopic Models Of the Traffic Flowsmentioning
confidence: 99%